Axonal protection by short-term hyperglycemia with involvement of autophagy in TNF-induced optic nerve degeneration - Sase, Kana; Kitaoka, Yasushi; Munemasa, Yasunari; Kojima, Kaori; Takagi, Hitoshi (Frontiers in Cellular Neuroscience, 2015)
Previous reports showed that short-term hyperglycemia protects optic nerve axons in a rat experimental hypertensive glaucoma model. In this study, we investigated whether short-term hyperglycemia prevents tumor necrosis factor (TNF)-induced optic nerve degeneration in rats and examined the role of autophagy in this axon change process. In phosphate-buffered saline-treated rat eyes, no significant difference in axon number between the normoglycemic (NG) and streptozotocin-induced hyperglycemic (HG) groups was seen at 2weeks. Substantial degenerative changes in the axons were noted 2 weeks after intravitreal injection of TNF in the NG group. However, the HG group showed significant protective effects on axons against TNF-induced optic nerve degeneration compared with the NG group. This protective effect was significantly inhibited by 3-methyladenine, an autophagy inhibitor. Immunoblot analysis showed that the LC3-II level in the optic nerve was increased in the HG group compared with the NG group. Increased p62 protein levels in the optic nerve after TNF injection was observed in the NG group, and this increase was inhibited in the HG group. Electron microscopy showed that autophagosomes were increased in optic nerve axons in the HG group. Immunohistochemical study showed that LC3 was colocalized with nerve fibers in the retina and optic nerve in both the NG and HG groups. Short-term hyperglycemia protects axons against TNF-induced optic nerve degeneration. This axonal-protective effect may be associated with autophagy machinery.